REFLEKSI PARADIGMA ILMU-ILMU SOSIAL - Tjahyadi, Sindung (HUMANIKA, 2015)
This article discusses about a paradigm shift in the social sciences based on "the history of science" perspective. The key question is how the recent development of the discourse about the paradigms of the social sciences. The paradigmatic and methodological development forward directed through a post-empirical approach to the exclusion of desire unification cause or structure as the objective theory of social action, and develop a multi-theoretical paradigms on the basis of variations in the structure that can be applied to the various regions and types of action. Furthermore, elaborated further needed is to develop methodological pluralism and theoretical unification in the social sciences are expected to confirm the two sides of the comprehensive-pluralistic approach in the philosophy of social sciences. The main thing about the legitimacy of the methodology underlying the study is to examine the criteria on what should have knowledge of it. Finally, that the dimensions of "ontological" social science should be "liberated" from the illusion of objectivism